Synthesis and Potency Study of Some Dibutyltin(IV) Dinitrobenzoate Compounds as Corrosion Inhibitor for Mild Steel HRP in DMSO-HCl Solution - Hadi, Sutopo; Afriyani, Hapin; D. Anggraini, Wynda; I. Qudus, Hardoko; Suhartati, Tati (Asian Journal of Chemistry, 2015)
Following our succes in the synthesis of some derivatives of organotin(IV) carboxylates, in this work we reported the corrosion inhibitor study of three dibutyltin(IV) compounds using ligands of 2-, 3- and 4-nitrobenzoic acid. All the three synthesized compounds were characterized by spectroscopy techniques and also based on the microanalytical and physical data. The corrosion inhibition was evaluated with potentiodynamic polarization technique using ER644 Integrated Potentiostat eDAQ type on mild steel hot rolled plate (HRP) in DMSO-HCl solution. The results indicated that the these compounds showed interesting inhibition activity with percentage of inhibition efficiency (% IE) of 59.3, 60.5 and 61.2 % for dibutyltin(IV) 2-nitrobenzoate, 3-nitrobenzoate and 4-nitrobenzoate, respectively. These three dibutyltin(IV) compounds have been shown promising to be potentially used as anticorrosion inhibitors.